Influence of the Cut Axial Depth on Surface Roughness at High-Speed Milling of Thin-Walled Workpieces - A. I. Germashev; V. A. Logominov; S. I. Dyadya; Y. V. Kozlova; V. A. Krishtal (Наука и техника)
The paper presents the results of research on the dynamics of end milling of thin-walled work-pieces having complex geometric shapes. Since the milling process with shallow depths of cut is characterized by high intermittent cutting, the proportion of regenerative vibrations decreases, and the effect of forced vibrations on the dynamics of the process, on the contrary, increases. The influence of  axial depth of cut on the vibrations arising during processing, and roughness of the processed surface have been studied in paper.  The experiments have been carried out in a wide range of changes in the spindle speed at different axial cutting depths.  Vibrations of a thin-walled work-piece  have been recorded with an inductive sensor and recorded in digital form. Then an oscillogram has been used to estimate the amplitude and frequency of oscillations. The profilograms of the machined surface have been analysed. Roughness has been evaluated by the parameter Ra. The results have shown similar relationships for each of the investigated axial cutting depths. The worst cutting conditions  have been observed when the natural vibration frequency coincided with the tooth frequency or its harmonics. It is shown that the main cause of vibrations in high-speed milling  is forced rather than regenerative vibrations. Increasing the axial depth of cut at the same spindle speed increases the vibration amplitude. However, this does not significantly affect the roughness of the processed surface in cases when it comes to vibration-resistant processing.